2016
DOI: 10.1515/jpm-2015-0165
|View full text |Cite
|
Sign up to set email alerts
|

Intervention versus a conservative approach in the management of TRAP sequence: a systematic review

Abstract: Intervention either by cord occlusion or by ablation confers a better survival rate compared to conservative management. This appears more compelling if there are one or more poor prognostic features. Ablative techniques are superior to cord occlusion. There were insufficient data to determine which poor prognostic features should guide management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
0
8
0
6
Order By: Relevance
“…In the largest series on the outcome of 49 acardiac twin pregnancies without intrauterine surgical treatment the mortality rate was 51% and only 24% of the patients delivered after 36 gestational weeks [6]. Other studies described a 50-70% mortality rate without adequate treatment [7,8].…”
Section: Discussionmentioning
confidence: 97%
“…In the largest series on the outcome of 49 acardiac twin pregnancies without intrauterine surgical treatment the mortality rate was 51% and only 24% of the patients delivered after 36 gestational weeks [6]. Other studies described a 50-70% mortality rate without adequate treatment [7,8].…”
Section: Discussionmentioning
confidence: 97%
“…4, 26,27,[30][31][32] As odds with dichorionic twins, lethal malformations in MC twins can hardly be managed expectantly. 1 A systematic review of the literature reported a 12% (95% CI [7][8][9][10][11][12][13][14][15][16][17][18], P = .02) risk of the healthy survivor's demise following its abnormal co-twin's death 33 (Table 3). However, SF may increase the risk of losing the whole pregnancy in up to 5% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…There are three main options for managing cases of MC twins discordant for congenital anomalies (DCA): expectant management (EM), selective feticide (SF), or termination of the entire pregnancy (TOP). With EM, the potential loss of a malformed MC twin exposes the co-twin to intrauterine demise (10%-25%) or neurological injury (24%-45%) 8,9 whereas SF is not always safe and could result in the loss of the whole pregnancy in 5% of the cases. 10 To our knowledge, there is no study showing that one particular strategy is better than the other.…”
Section: Introductionmentioning
confidence: 99%
“…If the TRAP sequence is left untreated, a substantial proportion of pump twins die in utero up to 18 weeks of gestation, and 50% of the remainder die in the further course of pregnancy or in the neonatal period as a result of prematurity [ 12 ]. These fetal intervention techniques target the umbilical cord vessels, the intrafetal vessels, or the vascular anastomoses on the placental surface [ 12 , 13 ]. The optimal treatment technique and timing of intervention in pregnancies complicated with TRAP sequence are still debated [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%